From Referrals to Suspensions: New Evidence on Racial Disparities in Exclusionary Discipline - Jing Liu; Michael S. Hayes; Seth Gershenson (Institute of Labor Economics (IZA), 2021)
We use novel data on disciplinary referrals, including those that do not lead to suspensions, to better understand the origins of racial disparities in exclusionary discipline. We find significant differences between Black and white students in both referral rates and the rate at which referrals convert to suspensions. An infraction fixed-effects research design that compares the disciplinary outcomes of white and non-white students who were involved in the same multi-student incident identifies systematic racial biases in sentencing decisions. On both the intensive and extensive margins, minoritized students receive harsher sentences than their white co-conspirators. This result is driven by high school infractions and applies to all infraction types. Reducing racial disparities in exclusionary discipline will require addressing underlying gaps in disciplinary referrals and the sys tematic biases that appear in the adjudication process.
Keywords: I2; J7; 330; intentional discrimination; exclusionary discipline; office referrals